Identification of key events in baseball hitting using inertial measurement units - Punchihewa, N. G.; Yamako, G.; Fukao, Y.; Chosa, E. (Journal of Biomechanics, 2019)
Quantification of baseball hitting mechanics under game conditions help players to become successful batters and prevent injuries. Inertial measurement units (IMUs) can measure motion without any spatial restriction and are thus becoming a popular tool to investigate sports biomechanics. Biomechanical analysis of hitting requires the accurate detection of key events including "foot-off" while leaning back (FOff), "foot-on" during forward swing (FOn), and ball impact. Ten male university baseball players hit a ball suspended on a T pole five times in kick-hitting and glide-hitting styles. Three IMUs were attached on mid-pelvis and on each hand to record acceleration and orientation data. The key events identified by the three IMUs were compared with those retrieved by an optical motion capture system with force platforms. The timings of the local peak acceleration of the pelvis in the direction of the pitcher that were recorded by the IMU closely matched those of FOff and FOn events detected by the ground reaction force. Root mean square error (RMSE) between each measurement for the FOff and FOn events were 0.024 and 0.031 s, respectively. The timing of the negative peak of acceleration in the proximal direction of the hands corresponded to the impact time determined by an optical motion capture system. RMSEs for the knob and barrel-side hand were 0.009 and 0.011 s, respectively. Our results demonstrate how IMUs can be useful for analyzing baseball hitting mechanics.